1989
DOI: 10.1021/bi00431a050
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of phospholipid headgroups induced by a cationic integral membrane peptide as seen by deuterium magnetic resonance

Abstract: Deuterium nuclear magnetic resonance (2H NMR) was used to study the interaction of a cationic amphiphilic peptide with pure DMPC membranes and with mixed bilayers of dimyristoylphosphatidylcholine (DMPC) and dimyristoylphosphatidylserine (DMPS). The choline and serine headgroups were selectively deuteriated at the alpha and beta positions. The amphiphilic peptide, with 20 leucine residues in the hydrophobic core and two cationic hydrophilic lysine residues at each end, spanned the lipid bilayer. Although 2H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
116
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 24 publications
(49 reference statements)
18
116
0
Order By: Relevance
“…KALP23 has only a small effect on acyl chain order and dynamics, in agreement with work on a comparable Lysflanked polyleucine peptide (38,39). Nevertheless, earlier studies have shown that Lys-flanked polyleucine peptides are capable of inducing systematic acyl chain ordering and disordering (40,41).…”
Section: Discussionsupporting
confidence: 83%
“…KALP23 has only a small effect on acyl chain order and dynamics, in agreement with work on a comparable Lysflanked polyleucine peptide (38,39). Nevertheless, earlier studies have shown that Lys-flanked polyleucine peptides are capable of inducing systematic acyl chain ordering and disordering (40,41).…”
Section: Discussionsupporting
confidence: 83%
“…Figure 11 shows that, relative to the neutral case, cationic surface charge causes the P-N vector to tilt upward, whereas anionic surface charge causes the P-N vector to tilt downwards toward the bicelle surface. This is in accord with the earliest models of the phosphocholine response to surface charges 7,18 and with the analysis of the case of cationic surface charge by Akutsu and Nagamori. 21 Figure 12(A) shows that the average P-N tilt changes in a continuous fashion with increasing cationic or anionic surface charge, but that cationic charge produces a far greater absolute effect.…”
Section: Torsion Angle Analysis For the Case Of Charged Surfacessupporting
confidence: 89%
“…7,18 Interestingly, they predicted changes in the 13 C˛-31 P dipolar coupling for cationic versus neutral versus anionic surface charge that are confirmed here experimentally for the first time. Nevertheless, these authors concluded that observed quadrupolar splittings could only be reproduced if the phosphocholine group underwent internal torsion angle changes, rather than reorienting as a unit as postulated in the choline tilt model.…”
Section: Multiple Conformations Modelsupporting
confidence: 77%
See 1 more Smart Citation
“…This result can be compared with other deuterium NMR studies of the interaction between PS and various proteins [20][21][22]301, which show that positively charged proteins which do not penetrate within the bilayer have detectable (though weak) effects on the conformation of PS head group [20,21]. Proteins which are both charged and able to penetrate into the membrane surface have a much larger effect on the conformation of PS head group [30]. The absence of any effect of spectrin on the conformation of PS head group suggests that the interaction of spectrin with these lipids is purely superficial and has no hydrophobic component, despite the presence of some hydrophobic segments on the protein [31].…”
Section: Discussionmentioning
confidence: 66%